Legal Implications of the Annulment of Land Grant Deeds and the Liability of the Land Deed Official in Deed Execution - Febrina Dwi Hendrawani; Mutia Kirana Aprilia (Warmadewa Press, 2025)
This research examines the legal implications of the annulment of land grant deeds and the liability of the Land Deed Official within the context of Indonesian civil law, particularly under Articles 1666–1693 and Article 1320 of the Indonesian Civil Code. The annulment of a grant deed, often resulting from a violation of Article 1668—which prohibits the grantor from retaining control over the granted property—renders the deed null and void ipso jure, restoring ownership rights to the grantor through restitutio in integrum and cancelling the related land certificate in accordance with the Indonesian Regulation of the Minister of Agrarian Affairs No. 3 of 1997. This study employs a normative juridical approach using statutory, conceptual, and case-based methods, highlighting the weak verification practices of Land Deed Officials, which often trigger disputes and legal uncertainty, thereby undermining the principle of legal certainty as stipulated in Article 19 of the Indonesian Basic Agrarian Law. The liability of the Land Deed Official encompasses civil aspects under Article 1365 of the Indonesian Civil Code, administrative aspects under Government Regulation No. 24 of 2016, and ethical aspects; however, weak supervision exacerbates socio-economic losses. This research emphasizes the urgent need for reform, including strengthening the professional competence of Land Deed Officials, enhancing verification technology, and harmonizing relevant legal frameworks, in order to ensure the legality of land grant transactions, prevent disputes, and realize agrarian justice.